1989
DOI: 10.3758/bf03334629
|View full text |Cite
|
Sign up to set email alerts
|

A new instrument for measuring optimism and pessimism: Test-retest reliability and relations with happiness and religious commitment

Abstract: The main purpose of the present study was to assess the test-retest reliability of a newly devised instrument for measuring optimism and pessimism. In addition, correlations were obtained between the optimism and pessimism scores and two measures of happiness as well as with subjects' responses to single-item questions about the likelihood of a nuclear encounter and about their religious and political commitment and philosophy oflife. The instruments were administered to 106 introductory psychology students on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
51
1
3

Year Published

1991
1991
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(59 citation statements)
references
References 8 publications
4
51
1
3
Order By: Relevance
“…When individuals feel as though they make an impact, they are more committed (Mowday, Porter & Steers, 1982). Indeed, other forms of commitment relate to optimism such as religious commitment (Dember & Brooks, 1989), goal commitment (Werenfels, 2006;Montgomery, Haemmerlie, & Ray, 2003), and commitment to schoolwork (Hoekman, McCormick, & Barnett, 2005). We argue that when controlling for trait optimism, state optimism will be positively related to organizational commitment while trait affect will not significantly predict affective commitment when controlling for state optimism.…”
Section: Affective Commitmentmentioning
confidence: 86%
“…When individuals feel as though they make an impact, they are more committed (Mowday, Porter & Steers, 1982). Indeed, other forms of commitment relate to optimism such as religious commitment (Dember & Brooks, 1989), goal commitment (Werenfels, 2006;Montgomery, Haemmerlie, & Ray, 2003), and commitment to schoolwork (Hoekman, McCormick, & Barnett, 2005). We argue that when controlling for trait optimism, state optimism will be positively related to organizational commitment while trait affect will not significantly predict affective commitment when controlling for state optimism.…”
Section: Affective Commitmentmentioning
confidence: 86%
“…Thus, separate optimism and pessimism scores are produced by the instrument. Dember and Brooks (1989) reported that the test-retest reliability for the optimism scale was .75, whereas the test-retest reliability of the pessimism scale was .84.Additionally, these scales were shown to be significantly related to measures of happiness.The DAS consists of 15 true-false items. This instrument has been shown to have a test-retest reliability of .83 (Templer, 1970).…”
mentioning
confidence: 99%
“…The Revised UCLA Loneliness Scale is a 20-item scale that correlates significantly with scores on the Beck Depression Inventory and the CosteUo-Comrey Anxiety and Depression Scale (Russell et al . , 1980).The Dember et al . (1989) Optimism-Pessimism Scale consists of 56 items to which subjects indicate their degree of agreement.…”
mentioning
confidence: 99%
“…Several studies performed with this instrument pointed to controversial results regarding the construct unidimensionality and also for coincidences with neuroticism, trait anxiety, self-mastery and self-esteem (Chang, D'Zurilla, & Maydeu-Olivares, 1994;Dember & Brooks, 1989;Smith, Pope, Rhodewalt, & Poulton, 1989). Due to such criticisms, Scheier, Carver and Bridges (1994) revised the instrument, removing items that did not focus explicitly in expectations regarding the future.…”
Section: Introductionmentioning
confidence: 99%